(untitled) (RENTAS: Jurnal Bahasa, Sastera dan Budaya, 2024)
Taboo refers to social and behavioural proscriptions which may instigate discomfort in society, both in language use and psychical behaviour. In audiovisual translation, the emphasis on taboo is often placed on its relative audience reception and the enforcement of relevant laws and regulations. Akin to the nature of audiovisual products, subtitling taboo references also warrants multimodal consideration, especially in relation to both verbal and nonverbal elements. This study, in particular, aims to probe into the taboo language of subtitling from Malay into English. The film The Assistant (2022), which was released on the online streaming platform Netflix, is selected as the corpus. To this end, a parallel corpus was developed and subsequently analysed using AntConc and AntPConc. Frequency, thematic and translation strategy patterns were mapped and descriptively analysed. In general terms, the analysis reveals that the taboo words in the source text are multifaceted, predominantly exclamatory, and markedly explicit. Many of the taboo loads are also found to be equally rendered into the target text, which corresponds to Netflix’s no-censorship policy. The study also learns the omission of some references in the translation, which can be partly linked to the technical and structural constraints of subtitling.